Community-based participatory process evaluation based on the Reach, Quality Control, Fidelity, Satisfaction, and Management (RQFSM) model in Nevada: A study protocol - Asma Awan; Manoj Sharma (BioSocial Health Journal)
Introduction: The healthcare system in Nevada has rural-urban, racial-ethnic, economic, and other inequities in care. Social determinants of health (SDOH) have exacerbated health disparities among high-risk and underprivileged populations. This study protocol presents Nevada’s COVID-19 public health disparity reduction initiatives and community-based participatory process evaluation methodologies. The participatory process evaluation based on the Reach, Quality Control, Fidelity, Satisfaction, Management (RQFSM) Model has been planned with 25 partner organizations that deliver public health services within Nevada. Methods: This program evaluation will be conducted by the University of Nevada, School of Public Health in collaboration with the Nevada Office of Minority Health and Equity (NOMHE) and the State of Nevada Division of Public and Behavioral Health (DPBH), as primary agencies along with other partner organizations funded by the Centers for Disease Control and Prevention (CDC). A mixed-methods approach will be implemented to collect data from 25 partner organizations. For assessing the reach, quantitative and qualitative quarterly data collection reporting forms and focus group discussion (FGD) protocols will be designed; for quality control, fidelity, and management, semi-structured interviews and FGDs of project personnel and community members and process observation tally sheets will be generated, and for consumer satisfaction assessment, quantitative satisfaction surveys will be created in a participatory manner with all stakeholders. Results: The results of the protocol explain that community-based initiatives offer comprehensive, culturally competent, and high-quality primary healthcare services, while community health centers and other private sector groups can be considered as essential connections. Furthermore, it is anticipated that the necessity to integrate services like mental health, drug addiction treatment, pharmacies, disability assistance, and health care for older individuals would be acknowledged. This integration will be particularly crucial in places where access to reasonably priced healthcare is hampered by cultural, geographic, or economic restrictions. Conclusion: In this study, we describe the protocols of this community-based participatory process evaluation based on the RQFSM Model in Nevada